Antecedents of Patient Satisfaction with Outpatient Pharmacy Services on Patient Well-Being and Hospital Image - Austin, Ryan; Antonio, Ferdi; Pebriana, Regina (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
This study examined the influence of patient satisfaction with outpatient pharmacy services on patient well-being and hospital image, focusing on pharmacy location, service time, pharmacist attitude, medication supply, and medication teaching. A survey with cross-sectional data was conducted using a questionnaire modified from Khudair & Raza (2013). Data from 115 respondents were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). Pharmacy location and medication supply negatively impacted patient satisfaction. Service time, pharmacist attitude, and medication teaching had positive, significant impacts. Patient satisfaction positively influenced the hospital's image and patient well-being. Efficient service time, positive pharmacist attitude, and effective medication teaching enhanced patient satisfaction, improving hospital image and patient well-being. The study concluded that optimizing service time, pharmacist attitude, and medication teaching in outpatient pharmacy services could significantly enhance patient satisfaction, thereby improving patient well-being and hospital image.